The secret of the magic gourd [videorecording (DVD)] - Zhu, Jiaxin; Zhu, Jiaxin; Lin, Jitao (Screenwriter); Jin, Peida; Chen, Zhiying; Leung, Gigi, 1976-; Zhu, Qilong, 1994-; Guo, Kaimin, 1958-; He, Qing, 1964 January 13-; Meng, Qian, actress; Bleu, Corbin, 1989-; Hilty, Megan; et al. (Disney DVD., 2009)
When an inquisitive 11-year-old discovers a magical gourd while fishing, he has no idea of the trouble that lies at the end of his hook. As they share a series of amazing adventures, the boy learns an unforgettable lesson from an extraordinary friend.